Dark traits from the variable-centered and person-centered approach and relations with some risky behaviors - Dinić, Bojana M.; Velimirović, Mina; Sadiković, Selka (Psihološka istraživanja, 2019)
The main aim of this study was to identify latent profiles based on the Dark Triad and Dark Tetrad traits in a non-clinical sample. The second aim was to validate obtained profile solutions via their relations with risky behaviors known to be associated with dark traits - aggression and alcohol use. On the sample of 624 participants (48.2% males), Dark Triad Dirty Dozen - DTDD, Short Sadistic Impulse Scale - SSIS, Varieties of Sadistic Tendencies Scale - VAST, Reactive Proactive Questionnaire - RPQ, and questions about alcohol use were applied. Latent profile analysis revealed one profile or two quantitatively different profiles (low and high dark traits), suggesting that the variable-centered approach is more appropriate than the person-centered for describing the dark traits, at least when DTDD was used. In the case of Dark Tetrad, profile membership largely depended on the used sadism measure, i.e. profile agreement was moderate. High dark traits profile based on the combination with SSIS sadism scale was characterized by both higher aggression and alcohol use, while the same profile based on the combination with VAST sadism measure was characterized only by higher aggression.